50 years [compact disc] : the gold anniversary collection. - Darin, Bobby; Sledge, Percy; Franklin, Aretha; Rodgers, Nile; Nicks, Stevie; Midler, Bette; Brandy, 1979-; Lieber, Jerry; Charles, Ray, 1930-2004; Weill, Kurt, 1900-1950; King, Ben E.; Pickett, Wilson; et al. (Atlantic, 1998)
Compilation of hits from the Atlantic Record company over a fifty year span.